Prevalence of shoulder pain in Swedish flatwater kayakers and its relation to range of motion and scapula stability of the shoulder joint - Johansson, A.; Svantesson, U.; Tannerstedt, J.; Alricsson, M. (Journal of Sports Sciences, 2016)
Few studies have investigated the incidence of injuries in kayakers. The aim was to study the prevalence of shoulder pain in competitive flatwater kayakers and to evaluate any differences in range of motion or scapula stability of the shoulder joint among kayakers with or without the history of shoulder pain. Thirty-one kayakers were participated in the study, and a questionnaire including background data was used. Shoulder range of motion was measured with a goniometer, and the participants were observed for scapula dyskinesis in flexion and abduction. Of the participating kayakers, 54.8% (n = 17) had experienced shoulder pain. Kayakers who had experienced shoulder pain showed a significantly lower degree of internal rotational range of motion versus kayakers with no reported shoulder pain, with a mean degree of internal rotation in the right shoulder 49.3 vs 60.0 (P = 0.017) and the left shoulder 51.9 vs 66.0 (P = 0.000). Kayakers who had experienced shoulder pain were also observed with a scapular dyskinesis (n = 15 of 17 kayakers) to a significantly higher degree (P = 0.001) than kayakers with no reported shoulder pain. Findings suggest that screening for scapular dyskinesis and testing for rotational range of motion in the shoulder joint is essential in order to treat and maybe prevent shoulder pain in kayakers.